Efektivitas Penggunaan Modul Matematika Yang Bernuansa Islami untuk Memfasilitasi Kemampuan Pemecahan Masalah Matematis - Sarkawi, M. Rafki; Permana, Dony (JEMS: Jurnal Edukasi Matematika dan Sains, 2022)
Learning during the Covid-19 pandemic has made it difficult for MTs educators to hone students' mathematical problem-solving skills and difficulties in instilling Islamic values in students. One solution that educators can use in learning during the Covid-19 pandemic is to use modules. The module is one of the teaching materials that have the characteristics of independent learning principles. The purpose of this study is to see the effectiveness of the use of Islamic nuanced mathematics modules in facilitating students' mathematical problem-solving abilities. The type of this research is pre-experimental research and the research design is the one-group posttest-only design. Sampling is purposive sampling, which takes one class directly from the population as the research sample. The subjects of this study were students of class VII.1 at MTsN 1 Tanah Datar, totaling 24 people. The effectiveness of the mathematics module is seen from the classical completeness of the students' mathematical problem-solving ability test results. The classical completeness of the students' mathematical problem-solving ability test scores obtained is 70.08%. Because 70.08% > 60.00%, these results indicate that the use of Islamic nuanced mathematics modules is effective in facilitating students' mathematical problem-solving abilities.